A study on relationship between cash opportunity cost and financial flexibility - Hassan Ghodrati; Syed Ali Lajevardi; Abbas Gaeini (Management Science Letters)
This study evaluated the relationship between cost and performance yield investment opportunities, cash and financial flexibility bank pays. For this study, a sample of 94 companies from companies that are part of corporate clients BSI was selected using random sampling technique. In addition, to measure the performance, three measures of economic value added, return on assets and return on equity were used. The study evaluated the relationship between cash and the opportunity cost efficiency as well as financial flexibility to invest in BSI over the period 2007-2012. Statistical methods used in this study were panel data regression. Four hypotheses were proposed to achieve the goals and the results showed that the opportunity cost of holding cash investments with financial flexibility and efficiency were inversely associated with financial performance.